Punjab Public Management Reform Program : Program for Results Operation, Detailed Technical Assessment - World Bank (Washington, DC, 2014)
This document includes the full Technical Assessment of the Punjab Public Management Reform Program. The Assessment is based on the technical analysis of the Program. It covers: the strategic relevance and technical soundness of the proposed Program; the Program's results framework and monitoring and evaluation; the Program s governance structure and institutional arrangements; and the economic justification of the Program. It also presents an evaluation of the technical risks, and defines the improvements proposed as part of the Program Action Plan.